Characterisation of 6-DMATSMo from Micromonospora olivasterospora leading to identification of the divergence in enantioselectivity, regioselectivity and multiple prenylation of tryptophan prenyltransferases. Issue 41 (29th September 2016) - Winkelblech, Julia; Xie, Xiulan; Li, Shu-Ming
Abstract : Identification of a new tryptophan prenyltransferase 6-DMATSMo and different behaviours of DMATS enzymes for regiospecific mono- and diprenylations ofl - andd -tryptophan as well as methylated derivatives. Abstract : Prenylated secondary metabolites including indole derivatives usually demonstrate improved biological and pharmacological activities, which make them promising candidates for drug discovery and development. The transfer reactions of a prenyl moiety from a prenyl donor, e.g. dimethylallyl diphosphate (DMAPP), to an acceptor is catalysed by prenyltransferases. One special group of such enzymes uses DMAPP and tryptophan as substrates with dimethylallyltryptophans as reaction products and functions therefore as dimethylallyltryptophan synthases (DMATSs). Sequence homology search with known tryptophan prenyltransferases from Streptomyces led to identification of a putative prenyltransferase gene MolI14.36 in Micromonospora olivasterospora . Expression and biochemical investigations revealed that MolI14.36 acts as a tryptophan C 6-prenyltransferase (6-DMATSMo ). Study on substrate specificity of 6-DMATSMo displayed a significantly high activity towardsd -tryptophan, which prompted us to carry out comparative studies on enantioselectivity, regioselectivity and multiple prenylation ability of additional DMATSs including FgaPT2, 5-DMATS, 5-DMATSSc, 6-DMATSSv, 6-DMATSSa and 7-DMATS towardsl - andd -isomers of tryptophan and their analogues. The relative activities of the tested enzymes towardsd -tryptophan differ clearly from each other. Incubation ofl -, d -isomers or the racemates of 5-, 6- and 7-methyltryptophan revealed distinctly different preferences of the DMATS enzymes. Interestingly, 6-DMATSMo and 5-DMATSSc accepted 5-methyl-d -tryptophan much better than thel -enantiomer. Furthermore, the conversion yields of thed -isomers were strongly inhibited in the reactions with racemates. More interestingly, the regioselectivities of FgaPT2, 5-DMATSSc and 7-DMATS towardsd -tryptophan and its C 5-methylated derivative differed clearly from those of thel -forms. In addition, both mono- and diprenylated products were clearly detected for 5-DMATSSc withl - andd -enantiomers of tryptophan and their methylated derivatives.